2021
DOI: 10.1007/s10439-021-02821-z
|View full text |Cite
|
Sign up to set email alerts
|

Time Window of Head Impact Kinematics Measurement for Calculation of Brain Strain and Strain Rate in American Football

Abstract: Wearable devices have been shown to effectively measure the head's movement during impacts in sports like American football. When a head impact occurs, the device is triggered to collect and save the kinematic measurements during a predefined time window. Then, based on the collected kinematics, finite element (FE) head models can calculate brain strain, which is used to evaluate the risk of mild traumatic brain injury. To find a time window that can provide a sufficient duration of kinematics for FE analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…For example, duration requirements for head impact counting are typically shorter than those for kinematic measurements, whereas requirements for measuring acceleration magnitudes are shorter than those for measuring the complete time-history needed to obtain velocity and displacement and tissue-level response from Finite Element (FE) models of the head. 48 When post-processing raw data, consider the output of the wearable device and the steps required to enable comparison with reference sensor data. In some cases, data are provided in a processed format that can be readily used for analysis, but in others, data are provided in raw format and must be post-processed.…”
Section: Specific Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, duration requirements for head impact counting are typically shorter than those for kinematic measurements, whereas requirements for measuring acceleration magnitudes are shorter than those for measuring the complete time-history needed to obtain velocity and displacement and tissue-level response from Finite Element (FE) models of the head. 48 When post-processing raw data, consider the output of the wearable device and the steps required to enable comparison with reference sensor data. In some cases, data are provided in a processed format that can be readily used for analysis, but in others, data are provided in raw format and must be post-processed.…”
Section: Specific Considerationsmentioning
confidence: 99%
“…This level of validation is recommended because it enables the calculation of head injury criteria and tissue-level response from FE models from head kinematics measured by wearable devices. 48 For validation of impact counting as a binary classification problem, studies have reported sensitiv-ity, specificity, accuracy, and precision as common summary statistics. 95 Linear regression of peak kinematics has been commonly applied to determine the agreement between device and reference measurements, where the slope, intercept, and the coefficient of determination (R 2 ) are usually reported to quantify the strength of the correlation.…”
Section: Specific Considerationsmentioning
confidence: 99%
“…Several computational studies have also reported strain rate as an appropriate predictor for brain injury [27,29,32,36,71]. However, most TBI studies didn't report details of strain rate calculation [8,21,22,[71][72][73][74], making an appropriate interpretation of strain rate results impossible. For the handful of investigations with the strain rate calculation procedures elaborated, disparate inconsistency was noted in the computational scheme, posing inevitable challenges while comparing strain rate-related finding across studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the large body of literature that merely examined the strain-based outputs (e.g., the studies by Zhou et al (2020) and Bian and Mao (2020)). For those investigations with a focus on strain rate, it is ubiquitous that the strain rate values are directly reported without any clarification on how they are calculated (Beckwith et al, 2018; Kleiven, 2007a; Liu et al, 2021; Mao et al, 2006; McAllister et al, 2012; Post et al, 2015; Viano et al, 2005). Even when limiting to the handful of studies with the strain rate computational schemes elaborated, alarming inconsistency existed.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Computer modeling has also been utilized to evaluate tissue level brain strain, and intracranial displacement has been physically measured through postmortem human surrogates. 8,10,14 Advances in computer modeling and injury metrics will facilitate helmet improvement and has the potential to reduce the number of concussions observed in sports.…”
mentioning
confidence: 99%